2019
DOI: 10.12659/ajcr.913388
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer with Pituitary Metastasis Presenting as Secondary Adrenal Insufficiency: A Case Report and Literature Review

Abstract: Patient: Male, 62 Final Diagnosis: Pituitary metastasis of small cell lung cancer Symptoms: Blurred vision • weakness Medication: — Clinical Procedure: — Specialty: Oncology Objective: Unusual clinical course Background: Pituitary gland metastasis is rarely the initial presentation of metastatic cancer. Most cases of pituitary gland metastasis are asymptomatic with diabetes ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…At present, there are no uniform standards advocating postoperative radiotherapy and chemotherapy. However, an exceptional case was reported by Atallah-Yunes et al [ 12 ], in which radiotherapy resulted in a significant reduction in tumor size. Finally, a study by Caponnetto et al [ 13 ] confirmed that hyperprolactinemia may be one of the factors of poor prognosis of tumors metastatic to the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no uniform standards advocating postoperative radiotherapy and chemotherapy. However, an exceptional case was reported by Atallah-Yunes et al [ 12 ], in which radiotherapy resulted in a significant reduction in tumor size. Finally, a study by Caponnetto et al [ 13 ] confirmed that hyperprolactinemia may be one of the factors of poor prognosis of tumors metastatic to the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the convolutional neural network demonstrates good image segmentation results, indicating that it should be suggested in clinical MRI image analysis [17,18]. In this study, the traditional and improved DenseNet networks were applied to segment MRI images of PN patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cases without detailed neuro-ophthalmological examinations. Forty-four cases from 38 papers reported the presenting neuro-ophthalmological symptoms, such as visual field defects, vision loss, diplopia, and ophthalmoplegia, were selected [ 1 , 2 , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. The patient information, including age, sex, the time elapsed from primary cancer to the diagnosis of PM, sites of metastasis, treatment, and survival time after diagnosis of PM, were collected ( Supplementary material ).…”
Section: Methodsmentioning
confidence: 99%